Due to Instability Gambling is the best Model for most Financial Products - Klinkova, Galiya; Grabinski, Michael (Archives of Business Research, 2017)
In financial markets the demand curve is positively sloped in most cases. We give a rigorous mathematical prove that this leads to an instable equilibrium price. Therefore stock prices may fluctuate chaotically, making them unpredictable in many cases. Financial investments have therefore lots in common with gambling. In order to take the analogy further, we suggest a special gambling strategy (betting on a color in roulette). In doing so we have a model which may create a substantial amount of cash each year until it crashes after many years. Both gambling and financial speculation will never create money in the very long run. Because our gambling model is at least statistically predictable, it is “better” than speculative investment.